Endovascular Parent Artery Occlusion for Intracranial Aneurysms is a Viable, Cost-Effective Alternative: An Institutional Experience from Northeast India - Phukan, Pranjal; Sarma, Kalyan; Lynser, Donboklang; Sharma, Barun Kumar; Baruah, Deb Kumar; Saikia, Bishwajit; Singh, Binoy Kumar (Acta medica Lituanica, 2021)
Purpose. Endovascular parent artery occlusion (PAO) may be an alternative approach for complex intracranial aneurysm with potentially life-threatening complications. Moreover, the long-term follow-up of the PAO for an intracranial aneurysm is reported sparingly, limited to the case series. It is therefore important to carry out more research on long-term follow-up of the implication of PAO of intracranial aneurysm. The aim of the study was to analyses our experience of PAO for intracranial aneurysms with emphasis on long-term follow-up.Materials and Methods. The data of patients treated with PAO for intracranial aneurysms were reviewed. The outcome was evaluated based on aneurysmal occlusion on immediate angiography, follow-up magnetic resonance angiography (MRA), and complications. The modified Rankin score (mRS) was used to evaluate the functional outcome during the last follow-up. The mean, range, and standard deviation were reported for other variables – the patient’s age, number, and percentage.Results. Endovascular treatment was performed in 178 patients including PAO in 18 patients. Of these 18 (eighteen) patients, there were 13 dissecting aneurysms, 4 mycotic aneurysms, and one traumatic aneurysm.10 (ten) patients underwent PAO for proximal intracranial artery aneurysm and 8 (eight) patients for distal cerebral aneurysms. Complete occlusion of the aneurysm was achieved in 16patients (88.89%) and retrograde filling of the aneurysm was seen in 2 (11.11%) patients. One patient had intraprocedural coil migration resulting in a major infarct with an mRS of 2. Another patient (5.56%) had recanalization of the aneurysm and presented with rupture and intracranial hemorrhage with an mRS score of 4. The mRS of the other 16 patients (88.89%) was zero.Conclusions. Endovascular PAO for cerebral aneurysms was highly feasible and achieved complete occlusion. The morbidity and mortality rates were at the long-term follow-up also acceptable with negligible complications.
Keywords: Intracranial Aneurysm; Balloon Occlusion; Endovascular